The bug and the big heart -- Melioidotic pericardial effusion - Kuan, Leong Yew; Ng, Teck Han; How, Soon Hin; Kuan, Yeh Chunn (Malaysian Medical Associations, 2011)
Melioidosis is an infection caused by Gram negative bacterium Burkholderia pseudomallei leading to abscesses in lungs, liver, spleen, musculoskeletal system, prostate and sepsis. We present a rare case of purulent pericardial effusion caused by melioidosis with concomitant pneumonia and splenic abscesses. The patient underwent pericardiocentesis and successfully recovered from cardiogenic and septic shock.